Biofabricating murine and human myo‐substitutes for rapid volumetric muscle loss restoration. Issue 3 (15th February 2021) - Costantini, Marco; Testa, Stefano; Fornetti, Ersilia; Fuoco, Claudia; Sanchez Riera, Carles; Nie, Minghao; Bernardini, Sergio; Rainer, Alberto; Baldi, Jacopo; Zoccali, Carmine; Biagini, Roberto; Castagnoli, Luisa; et al.
Abstract: The importance of skeletal muscle tissue is undoubted being the controller of several vital functions including respiration and all voluntary locomotion activities. However, its regenerative capability is limited and significant tissue loss often leads to a chronic pathologic condition known as volumetric muscle loss. Here, we propose a biofabrication approach to rapidly restore skeletal muscle mass, 3D histoarchitecture, and functionality. By recapitulating muscle anisotropic organization at the microscale level, we demonstrate to efficiently guide cell differentiation and myobundle formation both in vitro and in vivo . Of note, upon implantation, the biofabricated myo‐substitutes support the formation of new blood vessels and neuromuscular junctions—pivotal aspects for cell survival and muscle contractile functionalities—together with an advanced muscle mass and force recovery. Altogether, these data represent a solid base for further testing the myo‐substitutes in large animal size and a promising platform to be eventually translated into clinical scenarios. Synopsis: The regenerative capability of skeletal muscle tissue is limited and significant tissue loss often leads to a chronic pathologic condition known as volumetric muscle loss. By exploiting the potentials of our biofabrication approach, one can manufacture advanced cell‐laden myo‐substitutes that ultimately may restore the functionalities of severely damaged skeletal muscles in vivo . Biofabricated myo‐substitutes may represent a valid candidate for volumetric muscle loss treatment. Upon implantation, biofabricated myo‐substitutes support the formation of new blood vessels and neuromuscular junctions together with an advanced muscle mass and force recovery. The employed biofabrication approach is compatible with human primary stem cells ‐ namely pericytes. Abstract : The regenerative capability of skeletal muscle tissue is limited and significant tissue loss often leads to a chronic pathologic condition known as volumetric muscle loss. By exploiting the potentials of our biofabrication approach, one can manufacture advanced cell‐laden myo‐substitutes that ultimately may restore the functionalities of severely damaged skeletal muscles in vivo .